2013
DOI: 10.1136/bcr-2013-010198
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis: an unusual presentation of acromegaly

Abstract: SUMMARYSecondary diabetes mellitus is known to occur in acromegaly due to insulin resistance caused by growth hormone excess. However, diabetes in acromegaly usually does not lead to ketosis. We describe an unusual case of a patient that presented with diabetic ketoacidosis in the emergency room with thirst, polyuria and dyspnoea. The patient was subsequently diagnosed with a growth hormone-secreting pitutary macroadenoma as the underlying pathology; after initial stabilisation with insulin and fluids, the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Diabetic ketoacidosis as an initial presentation of acromegaly documented in our subjects has been reported in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, in many of these reports, DKA occurred in subjects with prior diagnosis of acromegaly [9,[11][12][13][14][15]23].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Diabetic ketoacidosis as an initial presentation of acromegaly documented in our subjects has been reported in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, in many of these reports, DKA occurred in subjects with prior diagnosis of acromegaly [9,[11][12][13][14][15]23].…”
Section: Discussionmentioning
confidence: 88%
“…In this disorder, serum ACTH and Cortisol levels are not suppressed by administration of a single overnight dose of dexamethasone 1 mg or daily administration of 2 mg (0.5 mg every 6 hours) for 2 days while higher daily dose, 8 mg or 16 mg promptly induces suppression [7]. Finally, the finding of suppression of HGH and IGF1 concentrations by severe hyperglycemia in acromegaly is not documented in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current knowledge and available reports suggest that an atypical presentation of DKA is quite unusual. An interesting initial presentation of an acromegaly patient with DKA due to prolonged hyperglycemia was previously reported (5). However, reports of meningeal irritation associated with DKA are extremely rare (6) Several authors have suggested that cerebral edema associated with DKA may cause meningeal irritation in DKA (7-9).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the insulin requirement was transient even in the course of rhGH therapy in our patient, it is difficult to consider GH as the sole factor responsible for deterioration of glucose metabolism. Diabetic ketoacidosis can complicate cases with excess GH secretion such as gigantism or acromegaly ( 13 , 14 , 15 ). However, we found only one report of a patient developing diabetic ketoacidosis during GH therapy ( 16 ).…”
Section: Discussionmentioning
confidence: 99%